Pension Fund and a Faith that Promotes Justice in Indonesian Context - Rafael Mathando Hinganaday (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
According to the statistics, most of elderly people in Indonesia depend on younger generation to fulfil their daily needs. Many of them still need to work. Pension fund also gives little contribution for the elderly who previously worked at institutions. The level of knowledge on pension fund among Indonesians is still low, which also contributes on low participation in pension fund. Within this context, the Catholic Church in Indonesia implements concretely a faith that promotes justice. This is a literature review which aims to provide a deeper understanding on how Catholic pension fund institutions have implemented Catholic Social Teaching in Indonesian context, especially in the terms of “a faith that promotes justice”. This research uses pastoral circle scheme, which was popularized by Joe Holland and Peter Henriot, as a method for theologically reflecting the role of Catholic pension fund institutions in Indonesia. For this purpose, the author also learns from documents of the Church and the Society of Jesus, which express the slogan “a faith that promotes justice”. From the research, the author finds that only Laborem Exercens mentions clearly about people’s right to receive pension, when, at the same time, the Church also urges care for old people. Since this minimum regard for pension fund does not reflect real faith implementation of the Catholic Church related to social justice practices, especially care for old people and pensioners, Catholic pension fund institutions in Indonesia play a great role in sounding real concern of the Catholic Church.